AB1121 IMPLEMENTING HIGH VALUE CARE IN INPATIENT ANTINUCLEAR ANTIBODY TESTING. (2nd June 2020) - Mumtaz, S.; Li, Z. Y.; Yoon, J.; Yuvienco, C.
Abstract : Background: Antinuclear Antibody (ANA) testing forms the basis on which many rheumatological diseases are subsequently diagnosed. ANA testing quantifies the dilution of plasma to produce the titer and staining pattern and this can be a part of an ANA order set that reflexively cascades to sub-serology if positive. Studies have shown that a low titer ANA may potentially translate into an erroneous diagnosis: if one estimates a 1 percent prevalence of ANA associated disease in the general population then 30% of those individuals would have a false positive result of ANA detected at 1:40 titer [1]. We theorized that there is no need for several methods to coexist within a single inpatient hospital setting especially since diagnostic value of staining patterns alone is limited. Objectives: To compare the utility and yield of "ANA screening reflex to profile" (ARP) and "ANA reflex to titer" (ART) order sets in the inpatient setting of a community tertiary care hospital. We aim to identify the appropriateness of the ANA testing ordered including cost-effectiveness of ordering ARP over ART in order to implement the identified quality measures towards improving utilization of ANA testing. Methods: We identified all inpatient ANA reflex testing orders performed at Community Regional Medical Center, Fresno, California completed between 11/2018 till 07/2019. This included ART and ARP orders with 6 sub-serologies: SSA, SSB, dsDNA, Smith, Scl-70 and U1RNP. A Health Information Management report was generated which included patient's age, gender, length of hospital stay, dates of testing ordered, principal diagnosis and type of ANA testing ordered. Descriptive statistics were computed and analyzed. Results: We reviewed a total of 1, 012 ANA lab orders performed between 11/01/2018 until 07/30/2019 performed on 700 patients. According to the laboratory standard using Immunofluorescence Assay, an ANA titer starting from 1:40 is reported as positive. Out of the 1, 012 tests, 334 tests were positive i.e. 33%. The ART order by itself contributed to 29.9% of the positive testing while ARP formed 70% of the positive testing. 56 of the 910 ARP (6%) performed had one or more sub-serology antibody positive while in 178 ARP orders (20%) only the ANA titer was positive with negative serology. The most common sub-serology antibody noted positive was dsDNA forming 54% of the positive serology results. Multiple testing was noted with 218 orders of ARP and ART being ordered on the same patient within the same week, which shows 21.5% of ANA lab orders were repetitive. Length of stay was noted to be more than 3 days for 89% of the patients who had repetitive testing, majority of those tests (99%) on the same day by the same medical provider. It cost 5.0 for an ART order that resulted negative and 5.0 for an ARP panel that resulted negative. It cost 10.0 for those patients who had both ART and ARP ordered with negative results. A positive ART result added 12.0 additional to the cost of each positive ANA profile (67.36) when both tests were ordered together. Conclusion: Our study findings reflect the need for using higher yield ANA testing that has been standardized. It demonstrated that physicians ordering the testing were not familiar with the ART vs. ARP, and the laboratory orders needed to be re-structured. We removed the ART from the inpatient Electronic Medical Record i.e. Epic system so that only the ARP order remained. This would prevent repetitive testing and reduce healthcare costs through reduction by at least 12.0 per positive ANA result and may also translate into reduced length of hospital stay. We were able to add Centromere Antibody (Ab) to the ANA profile sub serologies to standardize it further as it is an important part of Scleroderma diagnosis. References: [1]Range of antinuclear antibodies in "healthy" individuals. AU, Tan EM, et al. Arthritis Rheum. 1997; 40(9):1601 Disclosure of Interests: None declared